Analysis of the Relationship Between Burnout, Work Engagement and Job Security to Turnover Intention with Mediation of Job Satisfaction in Nursing Personnel at XYZ Hospital Jakarta - Karisma, Komang Ayu; Jayanegara, Oscar (Syntax Corporation, 2025)
High labour turnover rates in the health care sector are a major concern for human resource management. This phenomenon has an impact on the quality of health services, the workload for the remaining staff, and the cost of recruiting and training employees, so it is necessary to understand the factors that cause it. Therefore, this quantitative study aims to analyze the influence of burnout, work engagement, and job security on turnover intention mediated by job satisfaction in nursing staff using a cross-sectional approach. Purposive sampling was used to select 129 health workers in a private hospital in Jakarta. Data collected through online questionnaires were analyzed using the PLS-SEM analysis method. The results showed that burnout has a positive and significant effect on turnover intention as indicated by the T-statistic value >1.96 and P-value <0.05, while work engagement, job security, and job satisfaction have no effect on turnover intention with a T-statistic value <1.96 and P-value>0.05. In addition, job satisfaction cannot mediate the relationship between burnout, work engagement, and job security. This finding has practical implications, namely that hospital management HR professionals must be able to overcome burnout conditions among clerical staff at XYZ Jakarta Hospital. This is because from the results of this study, burnout is proven to be one of the factors that can affect the high and low turnover intention among nursing staff.